Construction of professional identity: motivation through experience as an oncological patient (Research, Society and Development, 2018)
The present study aims to reflect about how different personal and academic experiences contribute to the construction of professional identity in pediatric nursing. This research consists of an autobiographical narrative used as a tool to build formative memorial with a qualitative approach about personal contact with health as influencer of future academic option for nursing. The experience as a cancer patient in childhood raises the discussion of the influence of this experience in the subject of history, his academic and personal choices. The way the patient goes through this experience and the importance of this moment in its history presents itself as an important factor in future option for the care and as a promoter in the search for a more humane practice in the areas of health care. Personal experiences contributed greatly in defining meanings for important aspects involved in the act of caring, define the choice of health care and training of qualified professionals for the development of a human caring and empathic, revealing also the possible reflection on the influence of the actions of health professionals as references for assisted in building their identities and future choices.